2020
DOI: 10.1155/2020/1915231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity, and Correlates of Anaemia in Pregnancy among Antenatal Attendees in Warri, South-Southern Nigeria: A Cross-Sectional and Hospital-Based Study

Abstract: Introduction. Anaemia in pregnancy affects about half of all pregnant women globally and constitutes an important reproductive health issue. The World Health Organization estimates that the prevalence of anaemia in pregnancy varies from 53.8% to 90.2% in developing countries and 8.3% to 23% in developed countries. Anaemia in pregnancy is common in developing countries and prevalence statistics required for its effective management and control is not adequately available in Nigeria. Thus, this study seeks to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
4
27
2
Order By: Relevance
“…Omote et al . reported it to be 30.65 ± 5.52 years, which was much higher than the present study[ 25 ] In that study, the youngest was 12 years old and the oldest was 47 years, whereas in the present study youngest was 17 years and the oldest was 38 years old. The highest proportion of anaemia (63.3%) in the present study was observed among the <25 years age group.…”
Section: Discussioncontrasting
confidence: 86%
“…Omote et al . reported it to be 30.65 ± 5.52 years, which was much higher than the present study[ 25 ] In that study, the youngest was 12 years old and the oldest was 47 years, whereas in the present study youngest was 17 years and the oldest was 38 years old. The highest proportion of anaemia (63.3%) in the present study was observed among the <25 years age group.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding could be explained by poor antenatal care and low health educational level. Omote V. and et al (16) estimated that all anemic pregnant women in their study had mild or moderate anemia. Lin L. and et al (11) found that anemia in pregnant women were more prevalent in 3 rd trimester and more severe in 2 nd trimester.…”
Section: Discussionmentioning
confidence: 87%
“…(10) ,Wemakor A. (12) ,Youssry M. and et al (13) , Pinho-Pompeu M. and et al (14) , Anlaakuu P. and Anto F. (15) , Omote V. and et al (16) , Kassa G. and et al (17) , Karaoglu L. and et al (7) , Asrie F. (1) , Lebso M. and et al (18) , Lin L. and et al (11) , Stephen G. and et al (2) , and Sritippayawan S. and et al (8) estimated a prevalence rate of 58.7%, 50.6%,42%, 41.27%, 40.8%, 37.6%, 31.66%, 27.1%, 25.2%, 23.5%, 23.5%, 18%, and 17.5% respectively.…”
Section: Discussionmentioning
confidence: 97%
“…and ICMR Taskforce Multicenter Study[ 12 18 19 20 ] On the contrary, few recent studies done in African continent found the prevalence of anemia in pregnant women as low as 25.8% to 37.6%. [ 21 22 ] This variation may be due to various socio-demographic and comorbid conditions. Also, as our study participants are mainly poor from tribal population with low socioeconomic status, therefore the prevalence of anemia during pregnancy may be remarkably high.…”
Section: Discussionmentioning
confidence: 99%